What influences men's decision to have a prostate-specific antigen test? A qualitative study. - Rai, T; Clements, A; Bukach, C; Shine, B; Austoker, J; Watson, E (2007)
BACKGROUND: Current UK policy recommends informed decision making for prostate-specific antigen (PSA) testing. The process by which men decide to be tested warrants further investigation. OBJECTIVE: To determine the important influences on men's decision to have a PSA test. METHODS: Semi-structured interviews with 20 men who had raised the issue of testing for prostate cancer with their GP and undergone the PSA test. RESULTS: Men wanted to be tested primarily because they believed in the benefits of early diagnosis. Triggers for consulting the GP were the personal experiences of friends with prostate cancer, a desire to be proactive about health, media reports, a family history or ongoing urinary symptoms. Before consulting the GP, men's awareness was largely based on personal accounts and media stories and did not include much familiarity with the potential limitations of testing. Many had decided they wanted to be tested by the time they consulted their GP and this decision remained largely unaffected by the consultation. Men varied in the value they placed on receiving information about the benefits and limitations of PSA testing from their GP. CONCLUSIONS: Men who consult their GP about testing are often already committed to having the test. When information about the benefits and limitations of PSA testing is provided, at that stage it may be too late for it to play a part in their decision. Making balanced information available to men in the community may be a more effective way to promote informed decision making and to facilitate more useful discussions with the GP.